The effectiveness of Instagram Advertising for Digital Marketing Strategy: Systematic Literature Review - Rahayuningrat, Prahita Sri; Ardiani, Gusti Tia; Alisa, Juniar; Sugiarti, Rubiah; Taufik, Nuryanti (AIBPM Publisher, 2024)
This systematic literature review study aims to understand the effectiveness of Instagram advertising for digital marketing. It used online data from Google Scholar and Proquest with the keywords